Waist circumference and end‐stage renal disease based on glycaemic status: National Health Insurance Service data 2009–2018. Issue 1 (23rd December 2022) - Cho, Yun Kyung; Huh, Ji Hye; Moon, Shinje; Kim, Yoon Jung; Kim, Yang‐Hyun; Han, Kyung‐do; Kang, Jun Goo; Lee, Seong Jin; Ihm, Sung‐Hee
Abstract: Background: Obesity is associated with an increased risk of developing type 2 diabetes mellitus (T2DM) and end‐stage renal disease (ESRD). This study aimed to examine the effect of waist circumference (WC) on the risk for ESRD based on glycaemic status in a Korean population‐based sample. Methods: This cohort study with a 9.2‐year follow‐up period used a population‐based National Health Insurance Service health checkup database with approximately 10 585 852 participants who were followed up from 2009 to the time of ESRD diagnosis. WC was categorized into seven levels in 5‐cm increments, with Level 4 as the reference group. Glycaemic status was categorized into the following groups: normal fasting glucose (NFG), impaired fasting glucose (IFG), newly diagnosed T2DM, T2DM treated with ≤2 oral hypoglycaemic agents (OHAs) and diabetes treated with ≥3 OHAs or insulin. We calculated hazard ratios (HRs) and 95% confidence intervals (CIs) for ESRD according to WC values and glycaemic status of the participants. Results: The study finally included 10 177 245 patients with a mean age of 47.1 (13.8) years. The study population included 5 604 446 men (55.1%) and 4 572 799 women (45.9%). In total, 8.3% ( n = 877 143) of the study population had diabetes. During the mean follow‐up of 9.2 (1.0) years (93 554 951 person‐years of follow‐up), 23 031 individuals were newly diagnosed with ESRD. The ESRD risk increased in parallel with an increase in WC in participants without T2DM, that is, the NFG and IFG groups (adjusted HRs [95% CIs] of WC Levels 4, 5 and 6: 1.17 [1.09–1.26], 1.37 [1.25–1.51] and 1.84 [1.63–2.07] in the NFG group and 1.06 [0.97–1.16], 1.23 [1.10–1.38] and 1.80 [1.57–2.06] in the IFG group, respectively). In patients with T2DM, the risk for ESRD was significantly increased in those with a low WC (adjusted HRs [95% CIs] of WC Level 1: 2.23 [1.77–2.80], 3.18 [2.70–3.74] and 10.31 [9.18–11.59] in patients with newly diagnosed diabetes, patients on ≤2 OHAs and those on ≥3 OHAs or insulin, respectively). The association between WC and ESRD thus showed a J‐shaped pattern in patients with newly diagnosed T2DM and a U‐shaped pattern in those on ≤2 OHAs and on ≥3 OHAs or insulin. Conclusions: Central obesity substantially increases the risk of developing ESRD regardless of glycaemic status. The harmful effects of low WC only become significant with the progression of T2DM.